A Solitary Necrotic Lesion in A Man with Acute Myeloid Leukemia and neutropenia - H Reid, Holly; A Sweeney, Sarah; Y Chon, Susan (Journal of Dermatologic Research And Therapy, 2015)
A case of a solitary necrotic cutaneous lesion in a neutropenic patient with acute myeloid leukemia is described. The report discusses infectious and non‑infectious differentials, work‑up under immunosuppression, and targeted management.
Keywords: febrile neutropenia; neutropenic entrocolitis; stenotrophomonas pneumonia